English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please show work/explain!
Thank you!

2007-02-07 14:55:13 · 6 answers · asked by Licorice 4 in Science & Mathematics Mathematics

6 answers

(x+1)(x+5)=0
x=-1 or -5

2007-02-07 14:59:39 · answer #1 · answered by kelsey 7 · 0 1

x^2+6x+5=0

To complete the square, you must create a perfect square.
x^2 + 6x + 9 = 4. I added 4 to both sides, which made it a perfect square. Now, it can be factored to
(x + 3)^2 = 4. Take the square of both sides.
x + 3 = +- 2
Solve.
x + 3 = 2 or x + 3 = -2
x = -1 or x = -5.

2007-02-07 23:01:16 · answer #2 · answered by Anonymous · 0 1

To complete the square:

Take half of the middle term (half of six = 3).
Square that number to use for the third term (3 squared = 9)
Add or subtract the number you need in order to make the third term a 9 in this case.

x^2+6x+5=0
x^2+6x+5+4=0+4
x^2+6x+9 = 4
(x+3)(x+3)=4 Take square root of each side
x+3 = + or - 2
x = -1 or -5

2007-02-07 23:02:42 · answer #3 · answered by ecolink 7 · 1 1

first make 2 brackets with an "x" in them to separate the x^2
(x ) (x )
then you know the 2 numbers multiply to 5 is always 1 and 5 because 5 is a prime number. and you know that because 1+5=6 that makes up the 6x part so your answer should look like...

(x+1)(x+5)

see when you expand
x times x make x^2
x times 5 make 5x
1 times x make 1x or just x
1 times 5 make 5

Combine like terms (the 5x and x) to have 6x.

=x^2+6x+5

Now the zero part...

(x+1)(x+5) = 0
Since anything times 0 is zero one of the brackets must be a zero, so to get that... (x+1) = 0 or (x+5) = 0

So to get 0...
(x+1) .... [-1]+1 = 0
or
(x+5)... [-5]+5 = 0

Therefore x can equal to [-1] or [-5]

To Double check we can evaluate:

x = [-1] :
([-1]+1)([-1]+5) = 0
0(-6) = 0

OR~!

x= [-5] :
([-5]+1)([-5]+5)=0
4(0)=0

x can be 2 numbers when you are doing squares that equal to 0

Now...
Hope it helps xD~!

2007-02-07 23:10:09 · answer #4 · answered by Anonymous · 0 0

x^2+6x+9=-5+9 .... divide the middle term by 2 then square it and add that to both sides...
(x+3)^2=4

2007-02-07 23:03:58 · answer #5 · answered by Anonymous · 1 0

there should be an example like that in your book look it up and follow the steps.

2007-02-07 22:59:38 · answer #6 · answered by schs_spartan 3 · 0 1

fedest.com, questions and answers